PERCEPTION OF MEDICAL DOCTORS ON CHEST TUBE THORACOSTOMY SIMULATION MODEL - Phone Myint Hlaing; Thasaneeya Ratanaroutai Nopparatjamjomras; Suchai Nopparatjamjomras (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Chest tube thoracostomy is a common procedure that offers in patients with medical emergency conditions. Severe complications or even death can occur to the patients if medical doctors do not well perform and skillfully. This study aims to find medical doctors’ perception of the realistic features of the chest tube thoracostomy simulation model, which was developed by researchers. Methods: Fifteen Myanmar medical doctors were voluntarily to enroll in a half-day, chest tube thoracostomy workshop. Data of medical doctors’ perception was collected using a 5-points Likert’s scale self-evaluation survey form. In addition, the participants were asked to write their comments or suggestions for the realistic features of the chest tube thoracostomy simulation model. Results: Medical doctors’ perception on the realistic features of the chest tube thoracostomy simulation model was positive by responding as agree and strongly agree. All experts perceived as strongly agree in cost effectiveness of the model (100%) and using the model in the procedural training (100%). The postgraduate doctors responded to similar human sensations and complying procedural steps as agree (92.3%) in both statements. All experts rated to self-confidence (100%) as agree whereas thepostgraduate doctors responded to it as agree (84.6%). Participants preferred the structures of the simulation model and its educational values for the chest tube thoracostomy procedural skills training. They suggested to use this simulation model for training medical students. Conclusion: The perception of the medical doctors on the realistic features of the chest tube thoracostomy simulation model showed that this simulation model could use as an effective educational tool in the procedural skills training.